Enhancing the Future Public Health Workforce Through Competency-Based Student Field Placements - Michelle Carvalho; Laura Lloyd; Melissa Alperin; Lisa McCormick; Kathleen Miner (Georgia Southern University, 2017)
Background: The Public Health Workforce Interest and Needs (PHWINS) 2014 survey from ASTHO (Association of State and Territorial Health Officials) demonstrated a dramatic need for succession planning and retention of the future public health workforce. To address this need, the Region IV Public Health Training Center's (R-IV PHTC) Pathways to Practice Scholars Program places students from accredited schools and programs of public health into practical field placement positions across eight states. Skill- and competency-based student field placements reinforce the value of working with medically underserved areas/populations (MUA/Ps) through public health agencies. Field placements use adult learning theory through experiential learning to build essential skills from the Council on Linkage (COL) core competencies. Methods: Host agencies include state and local health departments, Area Health Education Centers, primary care settings, and community organizations in one of eight southeastern states serving MUA/Ps. Agencies propose practical projects using COL domains. Proposals are converted to job postings. Once an agency selects a student, the team collaboratively develops a detailed work plan using specific COL competencies. Results: A brief overview of evaluation findings will be shared but are not the focus of this workshop. Evaluation instruments included a pre-survey, work plan, mid-term survey, final evaluation, and alumni survey. Students submit a final report, reflection summary, webinar presentation and/or abstract worthy of submission to a professional conference. Findings demonstrated increases in students' perceived ability to perform core competencies and future plans to work in MUA/Ps. Conclusions: This program builds leadership and real-world experience in the future workforce while serving immediate needs of public health agencies. The workshop focuses on interactive discussion about processes and tools to create COL competencybased field placement position descriptions and detailed work plans. Participants can engage in dialogue about developing student positions which enhance their work while training the future workforce. Key words: student field placements, competencies, work plans